The Dynamics of Independence Post The Death of Father Among High-Achieving Students at IAIN Pontianak - Amalia, Kiki; Baroroh, Ema Zati; Sukmawati, Fitri; Syifa, Abdullah; Azzahrah, Syarifah Fathiyyah (Psychosophia: Journal of Psychology, Religion, and Humanity, 2025)
Father has a significant role in the family. The loss of the father caused a deep sadness for his son. This sadness can affect one's independence dynamics, especially in achievements. This study explored the development of independence and its impact on academic achievement in high-achieving students who had lost their fathers. Through qualitative case study research, two high-achieving students from IAIN Pontianak were investigated using in-depth interviews and observations. The data is analyzed by Milles and Huberman, which includes data reduction, data presentation, and conclusion. The findings revealed diverse experiences in the formation and development of independence. One participant established independence post-bereavement, which subsequently contributed to improved academic performance. Conversely, the other participant possessed pre-existing independence, which facilitated their adjustment and achievement following their father's death. Overall, the study underscores the crucial role of independence in shaping the academic trajectories of bereaved students. It highlights how independence, encompassing emotional, economic, intellectual, and social dimensions, not only enhances academic success but also equips students to navigate the challenges and emotional turmoil associated with parental loss.